Non-Newtonian behavior of a Colombian heavy crude oil: creep and interfacial rheology tests (2020)
Flow assurance in heavy crude oil is a challenge for the oil industry, given its high viscosity and low mobility. The present study shows the non-Newtonian behavior exhibited by a 13°API heavy crude oil when performing flow, oscillatory, and creep experiments. Flow testing shows increases in thixotropy as periods of stress and rest accumulate over 30 days. These changes are measured with the thixotropic area of the loop formed by the decay and recovery of viscosity. Oscillatory tests reveal the reversible nature of these viscosity changes since the bulk moduli do not change between loop tests. The viscoelastic effects of stress history are observed in the early stages of creep tests. These show a series of instantaneous elastic deformations that are understood as the solid-liquid transition in percolated structures. Interfacial shear rheology experiments with a surface coverage of 1,5 mg/m^2 show a structure that flows like a soft glass. The reproducibility of the linear viscoelastic zone of an interface with stress history provide evidence that the changes between shear-induced metastable states are reversible. The absence of hysteresis in flow tests probes that changes of structures with these characteristic times (0.2 s) are negligible in flow tests. The results suggest a connection between the thixotropy and the viscoelasticity of the crude oil, defined by the breakdown and reconstruction of the structures formed by the asphaltenes whose elastic contribution is visible only at low shear stress.